Synthesis and antimicrobial activity of 6-sulfo-6-deoxy-D-glucosamine and its derivatives. (7th August 2017) - Skarbek, Kornelia; Gabriel, Iwona; Szweda, Piotr; Wojciechowski, Marek; Khan, Muna A.; Görke, Boris; Milewski, Sławomir; Milewska, Maria J.
Abstract: 6-Sulfo-6-deoxy-D-glucosamine (GlcN6S), 6-sulfo-6-deoxy-D-glucosaminitol (ADGS) and their N -acetyl and methyl ester derivatives have been synthesized and tested as inhibitors of enzymes catalyzing reactions of the UDP-GlcNAc pathway in bacteria and yeasts. GlcN6S and ADGS at micromolar concentrations inhibited glucosamine-6-phosphate (GlcN6P) synthase of microbial origin. The former was also inhibitory towards fungal GlcN6P N-acetyl transferase, but at millimolar concentrations. Both compounds and their N -acetyl derivatives exhibited antimicrobial in vitro activity, with MICs in the 0.125–2.0 mg mL −1 range. Antibacterial but not antifungal activity of GlcN6S was potentiated by D-glucosamine and a synergistic antibacterial effect was observed for combination of ADGP and a dipeptide Nva-FMDP. Graphical abstract: Highlights: Synthesized 6-sulfo derivatives of D-glucosamine and D-aminoglucitol. Novel compounds inhibit glucosamine-6-phosphate synthase and exhibit antibacterial and antifungal activity. Synergistic antibacterial effect of novel compounds in combination with D-glucosamine was observed.